2009
DOI: 10.1093/glycob/cwp048
|View full text |Cite
|
Sign up to set email alerts
|

A complex, but uniform O-glycosylation of the human MUC2 mucin from colonic biopsies analyzed by nanoLC/MSn

Abstract: High-sensitivity glycan profiling providing detailed structural information is very important in the search for glycan disease markers. By combining a straight-forward and fast preparation protocol of mucins with high-throughput nanoLC/MS, we have been able to study the O-glycosylation of the colon MUC2 mucin from one single biopsy (approximately 5 mg wet tissue as starting material) collected from the sigmoid colon during routine colonoscopy of 25 normal control patients. This large mucin glycoprotein was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(152 citation statements)
references
References 29 publications
1
146
0
Order By: Relevance
“…For example human colonic MUC2 contains more than 100 different O-linked glycans, which range in size from to 2 to 12 monosaccharides, most of which are based on the core 3 structure. 28 Strikingly, the spectrum of these O-glycans was very uniform among human individuals. 28 In the oral cavity, it was demonstrated that the glycosylation of the salivary mucins MUC5B and MUC7 is heterogeneous and can differ between individuals even with the same blood group.…”
Section: Mucinsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example human colonic MUC2 contains more than 100 different O-linked glycans, which range in size from to 2 to 12 monosaccharides, most of which are based on the core 3 structure. 28 Strikingly, the spectrum of these O-glycans was very uniform among human individuals. 28 In the oral cavity, it was demonstrated that the glycosylation of the salivary mucins MUC5B and MUC7 is heterogeneous and can differ between individuals even with the same blood group.…”
Section: Mucinsmentioning
confidence: 99%
“…28 Strikingly, the spectrum of these O-glycans was very uniform among human individuals. 28 In the oral cavity, it was demonstrated that the glycosylation of the salivary mucins MUC5B and MUC7 is heterogeneous and can differ between individuals even with the same blood group. These different mucin glycoforms are secreted in the oral cavity by physically separated salivary glands.…”
Section: Mucinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ability to utilize mucin, the glycoprotein component of the mucous layer that covers the epithelial cells of the gastrointestinal tract, is limited to members of the B. bifidum species (21,24). Approximately 60% of the predicted glycosyl hydrolases encoded by B. bifidum PRL2010 are predicted to be involved in mucin degradation, most of which are conserved exclusively within the B. bifidum species (21).Host-derived glycoproteins such as mucin and proteoglycans (e.g., chondroitin sulfate and heparan sulfate), which are found in the colonic mucosa and/or human milk, are often highly sulfated (25)(26)(27)(28)(29). Human colonic mucin is heavily sulfated, which is in contrast to mucin from the stomach or small intestine, the presumed purpose of which is to protect mucin against degradation by bacterial glycosidases (30)(31)(32).…”
mentioning
confidence: 99%
“…Mucins in the intestine are O glycosylated by the addition of GalNAc to Ser and Thr moieties of the respective proteins, and further substitution of these GalNAc residues yields a diverse repertoire of glycan structures (29) that may be differentially glyco- sylated, dependent on their relative location within the intestine (30). Expression of blood group-related antigens that terminate in GalNAc are among glycans that exhibit varied expression in the gastrointestinal tract (31).…”
Section: Resultsmentioning
confidence: 99%